Argumentative tactic of rhetorical fallacies in political discourse - Hamad, Sa'ad Saleh; Mohamad Ali, Afida; Paramasivam, Shamala; Abdul Jabar, Mohd Azidan (DEWS Publication, 2022)
The world of political rhetoric is a murky one due to the use of faulty logic and unsound arguments. That is, detecting fallacies can be one of the challenges that face researchers in a given discourse. In political discourse, the speaker and in his effort to persuade his audience should utilize strong arguments based on truthful appeals. However, a speaker might be a good persuader by utilizing false appeals which may make people fall for them easily. Fallacies are deceptive tactics that the arguer may employ to convince the listener by violating reasonableness rules. This study followed a textual analysis method and adopted the Pragma-dialectical approach (PDA) proposed by Van Eemeren, Grootendorst, and Henkemans (2002) to determine the rhetorical fallacies in ten political speeches of Prime Minister Nouri al-Maliki; (i) identify the violated rules in committing such fallacies; (ii) determine the argument scheme that constructed such fallacies. The study found that al-Maliki violated most of the critical discussion rules and committed various rhetorical fallacies within these rules. The study concluded that the Pragma-dialectical approach can be used to analyze political discourse if we exclude rule two (burden of proof rule) and nine (closure rule). However, two types of fallacies were found to be absent in the Pragma-dialectical approach, indicating its lack of inclusivity. Henceforth, it is recommended to include these two types of fallacies within the Pragma-dialectical approach to enhance its inclusiveness.